An examination of the moral habitability of resource-constrained obstetrical settings. (September 2021) - Boakye, Priscilla N; Peter, Elizabeth; Simmonds, Anne; Richter, Solina
Background: While there have been studies exploring moral habitability and its impact on the work environments of nurses in Western countries, little is known about the moral habitability of the work environments of nurses and midwives in resource-constrained settings. Research objective: The purpose of this research was to examine the moral habitability of the work environment of nurses and midwives in Ghana and its influence on their moral agency using the philosophical works of Margaret Urban Walker. Research design and participants: A critical moral ethnography was conducted through the analysis of interviews with 30 nurses and midwives, along with observation, and documentary materials. Ethical considerations: After receiving ethics approval, signed informed consent was obtained from participants before data collection. Results: Five themes were identified: (1) holding onto the values, identities, and responsibilities of being a midwife/nurse; (2) scarcity of resources as limiting capacity to meet caring responsibilities; (3) gender and socio-economic inequities shaping the moral-social context of practice; (4) working with incoherent moral understandings and damaged identities in the context of inter- and intra-professional relationships; and (5) surviving through adversity with renewed commitment and courage. Discussion: The nurses and midwives were found to work in an environment that was morally uninhabitable and dominated by the scarcity of resources, overwhelming and incoherent moral responsibilities, oppressive conditions, and workplace violence. These situations constrained their moral agency and provoked suffering and distress. The nurses and midwives negotiated their practice and navigated through morally uninhabitable work environment by holding onto their moral values and commitments to childbearing women. Conclusion: Creating morally habitable workplaces through the provision of adequate resources and instituting interprofessional practice guidelines and workplace violence prevention policies may promote safe and ethical nursing and midwifery practice.